A review of New Zealand and southeast Australian echinothuriinids (Echinodermata: Echinothuriidae) with descriptions of seven new species - Anderson, Owen F. (Zootaxa, 2013)
Examination of a large collection of echinothurioid echinoids from museum collections in New Zealand and Australia re-vealed six new species in the genus Araeosoma (A. bidentatum sp. nov., A. migratum sp. nov., A. anatirostrum sp. nov., A. tertii sp. nov., A. leppienae sp. nov., and A. bakeri sp. nov.) and one in the genus Hapalosoma (H. amynina sp. nov.), while the recorded presence of A. coriaceum in northwest New Zealand was found to be incorrect. Several of the species described are rarely collected, their distribution being strongly associated with seamount type habitat in a relatively narrow depth range. The majority of the records of these new species are from the New Zealand region, with a strong centre of diversity revealed among the seamounts of the Bay of Plenty. The new species are clearly distinguished from known forms by characters of their pedicellariae, spines, coronal plate structure, colouring, and tuberculation. A key to the Echinothu-riinae of the region is included.